Simplified criterion to predict the lower bounds of the anisotropic ultimate strengths of 3D printing metals. (July 2023) - Zhang, Gonghe; Xu, Luoyu Roy
Highlights: Commonly used Tsai-Hill strength criterion mainly predicted the yield strength. Suggested quadratic strength criterion provided a lower bound of the ultimate strength. These results were verified by anisotropic ultimate strengths of major 3D printing metals. Abstract: 3D printing metals have an intrinsic building orientation, so they have some anisotropy in their strength due to the failure between the printing layers with direction dependence that was commonly seen in composite materials. Although the Tsai-Hill composite strength criterion predicted the ultimate strengths of some 3D printing metals made with selective laser melting and laser powder bed fusion (SLM/LPBF), the current study showed that the composite strength criterion was not applicable to the ultimate strength predictions of all 3D printing metals. Our suggested quadratic strength criterion without stress interaction provided conservative strength predictions to ensure safe 3D printing metal applications. Moreover, the shear strength plays a critical role in strength predictions and should be measured accurately.